2014
DOI: 10.1111/1574-6968.12493
|View full text |Cite
|
Sign up to set email alerts
|

Application of ΦSP-1 and ΦSP-3 as a therapeutic strategy againstSalmonellaEnteritidis infection usingCaenorhabditis elegansas model organism

Abstract: The potential of Salmonella-specific phages ΦSP-1 and ΦSP-3 as biocontrol agents was studied in vitro, employing host cell lysis test and in vivo, using Caenorhabditis elegans as a model organism. For in vivo testing, stage 4 C. elegans larvae were experimentally infected with the pathogen Salmonella. Worm mortality was scored for 10 days. TD50 (the time required for 50% of the nematodes to die) of infected worms in the presence of bacteriophages was comparable to uninfected worms, and the two phages provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Studies in bacteria‐eating nematodes (i.e. Caenorhabditis elegans ; Augustine et al ) or the larger wax moth ( Galleria mellonella ) larvae are becoming increasingly popular, due to their numerous advantages over higher animal models, including the lack of requirement for ethical approval, simple growth conditions and shorter life spans (Manohar et al ).…”
Section: Nonclinical Studiesmentioning
confidence: 99%
“…Studies in bacteria‐eating nematodes (i.e. Caenorhabditis elegans ; Augustine et al ) or the larger wax moth ( Galleria mellonella ) larvae are becoming increasingly popular, due to their numerous advantages over higher animal models, including the lack of requirement for ethical approval, simple growth conditions and shorter life spans (Manohar et al ).…”
Section: Nonclinical Studiesmentioning
confidence: 99%
“…Phage concentration in the CSF was 10-fold higher than that in blood, demonstrating the capacity of phages to cross the blood-CSF barrier; work in humans by Ghose et al (2019) has also recently confirmed this finding. Other studies have shown effective treatment of keratitis in mice (Furusawa et al, 2016), otitis media in dogs (Hawkins et al, 2010), sinusitis in sheep (Drilling et al, 2014), and systemic infections in zebrafish (Al-Zubidi et al, 2019;Cafora et al, 2019) and moth larvae (Hall et al, 2012;Augustine et al, 2014;Nale et al, 2016a;Manohar et al, 2018;Jeon et al, 2019), supporting the idea that phage therapy can be studied in a broad range of infection models and animal species.…”
Section: Other Infectionsmentioning
confidence: 82%
“…These results show that C. elegans can be a useful animal model for assessing the efficacy of phage therapy. 90 , 91 …”
Section: In Vivo Animal Trials Of Phage Therapymentioning
confidence: 99%